2018
DOI: 10.1098/rsif.2018.0653
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurements of three-dimensional trajectories and wingbeat frequencies of birds in the field

Abstract: Tracking the movements of birds in three dimensions is integral to a wide range of problems in animal ecology, behaviour and cognition. Multicamera stereo-imaging has been used to track the three-dimensional (3D) motion of birds in dense flocks, but precise localization of birds remains a challenge due to imaging resolution in the depth direction and optical occlusion. This paper introduces a portable stereo-imaging system with improved accuracy and a simple stereo-matching algorithm that can resolve optical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 48 publications
2
36
0
Order By: Relevance
“…In homing pigeons, for example, a 10-fold increase in the spatial density of a flock has been observed to be associated with a modest 0.1 Hz increase in wingbeat frequency, which was presumed to be accompanied by an energetic cost over the 7 flights that were observed [14]. Qualitatively similar effects have been observed in flocking jackdaws ( Corvus monedula ) and rooks ( Corvus frugilegus ) [17]. Flapping flight is the most energetically demanding form of sustained forwards locomotion that vertebrates perform [18,19], and flock dynamics may therefore have significant implications for individual energy expenditure and lifetime fitness.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In homing pigeons, for example, a 10-fold increase in the spatial density of a flock has been observed to be associated with a modest 0.1 Hz increase in wingbeat frequency, which was presumed to be accompanied by an energetic cost over the 7 flights that were observed [14]. Qualitatively similar effects have been observed in flocking jackdaws ( Corvus monedula ) and rooks ( Corvus frugilegus ) [17]. Flapping flight is the most energetically demanding form of sustained forwards locomotion that vertebrates perform [18,19], and flock dynamics may therefore have significant implications for individual energy expenditure and lifetime fitness.…”
Section: Introductionmentioning
confidence: 85%
“…Specifically, whereas pigeons flying in large cluster flocks increased their wingbeat frequency by 0.1 Hz across a range of increasing flock densities [14], our results show that the very act of flying with another bird increases a pigeon's wingbeat frequency by 1.0 Hz. A more recent study of flocking corvids [17] also found an increase in wingbeat frequency in large flocks, but compared this to data pooled from birds flying solo or in pairs, leaving open the question of how their wingbeat frequency would have changed relative to an unambiguous base line condition of solo flights.…”
Section: Discussionmentioning
confidence: 99%
“…The frame rate of the cameras (29.97 frames per second) and the FFT window determined a wingbeat frequency bin size of 0.12 wingbeats s −1 . Our method is similar to that used in a recent study of two corvid species (Ling et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…With recent technological advances in imaging technology, the study of animal aggregations has increasingly focused on the detailed observation of individuals within the group to provide simultaneous measurement of individual and group behaviour. For larger animals such as birds or fish, the task of tracking individuals can become challenging due to visual occlusions of individuals and potential large-scale translational movement of the group 4 . Many larger animals must also be studied in the wild, which brings additional complications.…”
Section: Background and Summarymentioning
confidence: 99%